Fabrication of carbon pasta elektroda composition modified with nanobentonite and nano TiO2 for niacinamide detection sensor - Anggraini Putri, Dhea; Setiarso, Pirim (Jurnal Pijar Mipa, 2023)
Niacinamide is the amide form of vitamin B3, which is usually analyzed for concentration using UV-Vis Spectrophotometry, HPLC, and KLT. The development of niacinamide analysis methods using cyclic voltammetry has not been widely studied. The use of working electrodes in cyclic voltammetry is usually carbon paste electrodes. However, these electrodes have disadvantages, relatively low sensitivity and slower electron transfer kinetics, so it is necessary to research working electrode modification to increase electrode sensitivity. This study aims to determine the effect of the addition of nanobentonite and nano TiO2 on carbon paste electrodes in improving electron transfer and electrode sensitivity in the analysis of niacinamide by cyclic voltammetry. Variations in electrode composition were conducted to determine the optimum composition in measuring niacinamide solution and the optimum pH in measuring niacinamide. Nanobentonite obtained from the synthesis using the sonochemical method produces an average particle size of 46.9 nm, and the composition of carbon, paraffin, nanobentonite, and nano TiO2 electrodes with a variation of 3:2:3:2 b/v has the highest current peak. The better the conductivity of the working electrode, the greater the maximum current peak produced due to the easy transfer of electrons for the reduction and oxidation reaction process. Using a buffer solution to adjust the pH of the niacinamide solution affects the analysis process, as evidenced by the IpA value at pH 7. The effect of pH variation also affects the stability of existing ions. So that the resulting current is higher, the higher the peak current value produced indicates, the more sensitive the electrode is due to high electron transfer. It maximizes the analysis of the concentration of the test solution because the measured concentration is linear with the measured current.